Do Personalised Campaigns Hint at Legislator Activities? The (Lacking) Relationship Between Campaigns and Legislator Behaviour in Hungary. Issue 4 (2nd July 2018) - Papp, Zsófia
Abstract: Campaigns, especially the level of personalisation is often perceived as a common tool for gathering extra votes. It may carry the promise of the representatives' tendency to deviate from the party line and focus on more particularistic activities such as constituency service. The main question of this article is whether we can expect MPs who personalise their campaigns to behave differently when elected than those following the party line during election time. I combine the Hungarian data from the Comparative Candidates Survey from 2010 with legislative data from the 2010–2014 parliament to test if more personalised campaigns culminate in a greater willingness to desert the party line at roll-call and a larger likelihood of representing constituency interests in parliament. Multivariate models indicate that personalisation has only a moderate effect on legislator attitudes and behaviour: campaigns are indicative only to how legislators perceive their jobs, and not how they actually carry out their tasks. Results suggest that even if voters had perfect information, they would not be able to infer how elected candidates are likely to behave when elected to office, which greatly challenges their ability to elect 'good' representatives.